Uso na modulação dos sistemas colinérgico e/ou serotonérgico e/ou gabaérgico de vertebrados, de um extrato bruto vegetal padronizado, composição farmacêutica para o tratamento de disturbios associados a disfunções do sistema colinérgico e/ou serotonérgico e/ou gabaérgico, e processo de produção de medicamento para a modulação dos sistemas colinérgico e/ou serotonérgico e/ou gabaérgico de vertebrados - Bolzani, Vanderlan da Silva [UNESP]; Souza, Ricardo Luis Nunes de (Instituto Nacional de Propriedade Industrial (INPI), 2008)
The present invention provides the use of molecules for cholinergic serotonergic and/or gabaergic system models, revealing pharmaceutical compositions comprising 11-OH-erythravine, erythravine, erythrartine, pharmaceutically acceptable isotherals, salts, byproducts and/or solvates thereof, optionally containing other Erythrine byproducts, for the treatment of anxiety disorders; processes for obtaining said pharmaceutical compositions...
Pharmaceutical compositions containing Erythrine mulungu derivatives and processes for their production
Processo: PI0504517-7
Processo: WO2007045060
Número de publicação: CN101330915 (A)
Número de publicação: CN101330915 (B)